2008
DOI: 10.1063/1.2929824
|View full text |Cite
|
Sign up to set email alerts
|

A minimum-reaction-flux solution to master-equation models of protein folding

Abstract: Master equations are widely used for modeling protein folding. Here an approximate solution to such master equations is presented. The approach used may be viewed as a discrete variational transition-state theory. The folding rate constant k f is approximated by the outgoing reaction flux J, when the unfolded set of macrostates assumes an equilibrium distribution. Correspondingly the unfolding rate constant k u is calculated as Jp u / ͑1− p u ͒, where p u is the equilibrium fraction of the unfolded state. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…When λ 1 << λ l for all l > 1, the transitions between the two states can be modeled well as rate processes, and the rate constants, k ± , are given by k+=ρBeqλ1;   k=ρAeqλ1 The equilibrium occupational probabilities of the two states are ρAeq=trueiAρieq;   ρBeq=trueiBρieq Instead of solving the eigenvalue problem, one can make a transition-state theory type estimate for k ± ; the presentation below follows the work of Zhou (2008). As indicated by the derivation in Subsubsection 3.1.1, a transition-state theory estimates k + by the normalized total reaction flux from state A to state B, assuming that the occupation of the microstates in state A is according to the equilibrium distribution.…”
Section: Unimolecular Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When λ 1 << λ l for all l > 1, the transitions between the two states can be modeled well as rate processes, and the rate constants, k ± , are given by k+=ρBeqλ1;   k=ρAeqλ1 The equilibrium occupational probabilities of the two states are ρAeq=trueiAρieq;   ρBeq=trueiBρieq Instead of solving the eigenvalue problem, one can make a transition-state theory type estimate for k ± ; the presentation below follows the work of Zhou (2008). As indicated by the derivation in Subsubsection 3.1.1, a transition-state theory estimates k + by the normalized total reaction flux from state A to state B, assuming that the occupation of the microstates in state A is according to the equilibrium distribution.…”
Section: Unimolecular Reactionsmentioning
confidence: 99%
“…Macromolecular crowding is expected o significantly affect kinetic properties of proteins and nucleic acids (Zhou et al, 2008). In general, macromolecular crowding can be treated implicitly by accounting for its effects on the energy functions and dynamics of the reactant molecules (Zhou, 2004; Minton, 1989).…”
Section: Macromolecular Crowdingmentioning
confidence: 99%
“…In the mechanism referred to as hydrophobic collapse, 23 a disordered loop forms first, giving rise to a native-like hydrophobic cluster, before the structure propagates in both directions to form the hydrogen bonds and the turn. The zipper mechanism is supported by a statistical mechanical model 33 and an analysis 34 of that model in which an approximate solution to the kinetic master equation is obtained based on a variational transition state theory. Monte Carlo simulations 35 of a lattice model using a local move set found that folding usually occurs via a zippering process, but sometimes via hydrophobic collapse.…”
Section: Introductionmentioning
confidence: 99%
“…Models based on a master equation have been successfully applied to simulate kinetic traps in related fields such as the folding kinetics of macromolecules. [12][13][14][15][16] Monte Carlo based methods are often used to solve instances of models involving master equations, 17,18 which rely on the computation of a large number of solution trajectories to approximate certain statistical properties of the system. Typical advantages of Monte Carlo based methods are: (a) identification of all possible connections between all states is not necessary as connected states can be determined on the fly during the simulation of a solution trajectory, and (b) there is no need to solve simultaneously a large number of stiff ordinary differential equations (ODEs).…”
Section: Introductionmentioning
confidence: 99%